2015
DOI: 10.1093/mnras/stv2171
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of two gravitationally lensed quasars in the Dark Energy Survey

Abstract: We present spectroscopic confirmation of two new lensed quasars via data obtained at the 6.5m Magellan/Baade Telescope. The lens candidates have been selected from the Dark Energy Survey (DES) and WISE based on their multi-band photometry and extended morphology in DES images. Images of DES J0115−5244 show two blue point sources at either side of a red galaxy. Our long-slit data confirm that both point sources are images of the same quasar at z s = 1.64. The Einstein Radius estimated from the DES images is 0.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…These other search methods are described in more detail in Agnello et al (2017). We provide here a brief summary: (1) the Gaussian Mixture Model (GMM) method of Ostrovski et al (2017),w h i c h uses supervised machine learning in a five-dimensional optical plus infrared color space and identified DES J0408-5354 as a candidate pair (D+G1 not found separately in J band due to blending noted above); (2) CHITAH (Chan et al 2015), which uses pixel-based automatic recognition on grizY cutout images and identified the system as a candidate pair (not flagged as a quad because the fourth image G2 is too red);and(3) the Artificial Neural Network method of Agnello et al (2015aAgnello et al ( , 2015b, which uses griz and W W 1 2 magnitudes and identified DES J0408-5354 as a candidate extended quasar. Figure 2 shows how the system was flagged by the GMM method as a candidate, due to the quasar-like colors of its components.…”
Section: Search and Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…These other search methods are described in more detail in Agnello et al (2017). We provide here a brief summary: (1) the Gaussian Mixture Model (GMM) method of Ostrovski et al (2017),w h i c h uses supervised machine learning in a five-dimensional optical plus infrared color space and identified DES J0408-5354 as a candidate pair (D+G1 not found separately in J band due to blending noted above); (2) CHITAH (Chan et al 2015), which uses pixel-based automatic recognition on grizY cutout images and identified the system as a candidate pair (not flagged as a quad because the fourth image G2 is too red);and(3) the Artificial Neural Network method of Agnello et al (2015aAgnello et al ( , 2015b, which uses griz and W W 1 2 magnitudes and identified DES J0408-5354 as a candidate extended quasar. Figure 2 shows how the system was flagged by the GMM method as a candidate, due to the quasar-like colors of its components.…”
Section: Search and Discoverymentioning
confidence: 99%
“…To date, we have discovered and spectroscopically confirmed three lensed quasar pair systems (Agnello et al 2015b;Ostrovski et al 2017) in DES. Here in this Letter we report the discovery and confirmation of the first lensed quasar quad (or quad-like) system, DES J0408-5354, in the DES.…”
Section: Introductionmentioning
confidence: 99%
“…Previous searches of the Dark Energy Survey data initially yielded six confirmed strongly lensed galaxies (Nord et al 2016) in the early DES data, and more recently yielded eight more(B. Nord et al 2017, in preparation), and four gravitationally lensed quasars (Agnello et al 2015;Lin et al 2017;Ostrovski et al 2017). Other SL systems discovered using the DECam imager include the Canarias Einstein Ring (Bettinelli et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our method (modified for use with grizY photometry) is one of several now being used to search for lenses in the Dark Energy Survey (Agnello et al 2015;Ostrovski et al 2017), which ought to produce at least as many lensed quasars as ATLAS. As no one method will be perfect, comparison of the results will shed light on their relative strengths and weaknesses.…”
Section: The Methodsmentioning
confidence: 99%